PERBANDINGAN SIKAP TERHADAP PERILAKU SEKS PRANIKAH ANTARA SISWA SMAN DENGAN SISWA MAN - Raden Reny Indrawaty (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2011)
The investigator feels interesting to know the differences attitude in SMA students and MA students to the pre marriage sex behavior. There is the indications shows that the adolescence attitude to the pre marriage sex is increasing. If we look the religion curriculum, there is the differences between the religion curriculum in SMA and MA. The students of SMA study religion much more than the students of MA. The research uses the comparative method and uses Mann Whitney U test. Based on the counting the degree of trust is 95% (α = 0,05) known that p> α. It means that Ho is accepted and H1 is rejected. From the result above shows that there is no attitude differences to the pre marriage sex behavior between the students at SMA and the students at MA. The average ranking between SMA and MA is 71,02 > 63,61.